KEBIJAKAN THE NEW SILK ROAD CINA DI BAWAH PEMERINTAHAN XI JINPING - Ni Putu Saraswati Puspita Dewi; Hikmatul Akbar (Jurusan Ilmu Hubungan Internasional, 2017)
Silk Road is an ancient trade route that connecting China and countries along Asia and Europe. China under President Xi Jinping wants to rebuild the ancient silk road by building various infrastructure such as highways, railways, ports, and gas pipelines. The development of this infrastructure aims to increase connection of Asian, European and African countries.